The Economic Burden of Brucellosis Care in China: Socioeconomic Status Inequality - He, Hai-Bo; Lu, Qiao-Shan; Wang, Lian-Lian; Aishan, Muhetal; Zhao, Jiang-Shan; Tang, Xian-Yan; Zhu, Man-Tong; Reheman, Milikam; Chen, Qiu-Lan; Zhang, Yan-Ping (Journal of tropical medicine, 2024)
The economic burden of brucellosis care on patients can lead to significant financial strain, despite partial coverage by medical insurance. However, there is limited research on the out‐of‐pocket costs faced by brucellosis patients. Therefore, our study aimed to investigate the costs and out‐of‐pocket expenses of brucellosis care, specifically examining the varying socioeconomic status of patients in Xinjiang, China. We collected cost and demographic data from 563 respondents and their hospital bills and employed latent variable analysis to assess socioeconomic status. The majority of patients belonged to the middle and lower socioeconomic status categories (85.97%), and they were primarily farmers and herders (82.77%). The median direct cost per brucellosis episode was USD 688.65, with out‐of‐pocket expenses amounting to USD 391.44. These costs exceeded both the 2020 Xinjiang and national per capita health expenditures (USD 233.66 and USD 267.21, respectively). Notably, the overall medical reimbursement rate was 48.60%, and for outpatient costs, it was merely 12.82%. Despite higher out‐of‐pocket costs among high socioeconomic status patients, the percentage of income spent was higher (37.23%) for patients in the lower socioeconomic status group compared to other groups (16.25% and 12.96%). In conclusion, our findings highlight that brucellosis patients are predominantly from the middle and lower socioeconomic status, with high out‐of‐pocket expenses placing them under significant financial pressure. Moreover, there is notable inequity in economic consequences across different socioeconomic status groups. These results call for policy interventions aimed at reducing brucellosis‐related poverty and promoting equitable access to care.